Comparing the reproducibility of commonly used magnetic resonance spectroscopy techniques to quantify cerebral glutathione. Issue 1 (16th April 2018) - Wijtenburg, S. Andrea; Near, Jamie; Korenic, Stephanie A.; Gaston, Frank E.; Chen, Hongji; Mikkelsen, Mark; Chen, Shuo; Kochunov, Peter; Hong, L. Elliot; Rowland, Laura M.
Abstract : Background: Cerebral glutathione (GSH), a marker of oxidative stress, has been quantified in neurodegenerative diseases and psychiatric disorders using proton magnetic resonance spectroscopy (MRS). Using a reproducible MRS technique is important, as it minimizes the impact of measurement technique variability on the study results and ensures that other studies can replicate the results. Hypothesis: We hypothesized that very short echo time (TE) acquisitions would have comparable reproducibility to a long TE MEGA‐PRESS acquisition, and that the short TE PRESS acquisition would have the poorest reproducibility. Study Type: Prospective. Subjects/Phantoms: Ten healthy adults were scanned during two visits, and six metabolite phantoms containing varying concentrations of GSH and metabolites with resonances that overlap with GSH were scanned once. Field Strength/Sequence: At 3T we acquired MRS data using four different sequences: PRESS, SPECIAL, PR‐STEAM, and MEGA‐PRESS. Assessment: Reproducibility of each MRS sequence across two visits was assessed. Statistical Tests: Mean coefficients of variation (CV) and mean absolute difference (AD) were used to assess reproducibility. Linear regressions were performed on data collected from phantoms to examine the agreement between known and quantified levels of GSH. Results: Of the four techniques, PR‐STEAM had the lowest mean CV and AD (5.4% and 7.5%, respectively), implying excellent reproducibility, followed closely by PRESS (5.8% and 8.2%) and SPECIAL (8.0 and 10.1%), and finally by MEGA‐PRESS (13.5% and 17.1%). Phantom data revealed excellent fits (R 2 ≥ 0.98 or higher) using all methods. Data Conclusion: Our data suggest that GSH can be quantified reproducibly without the use of spectral editing. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:176–183.